PHARMACOVIGILANCE STUDY OF ANTIRETROVIRAL THERAPY IN HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNODEFICIENCY SYNDROME PATIENTS AT ANTIRETROVIRAL THERAPY CENTRE, JABALPUR - Bansal, Rajkumari; K, Daryani K; Singh, Ajit Pratap (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to assess the adverse drug reactions (ADRs) of antiretroviral therapy along with its causality, severity, and preventability. Method: A prospective as well as a retrospective observational study with a sample size of 260, jointly conducted in the Department of Pharmacology and antiretroviral therapy (ART) center of N.S.C.B. Medical College Jabalpur, India, from March 2016 to July 2017. We observed various ADRs to ART in human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients and assessed causality, severity, and preventability of the reported ADRs as per the standard scales. Results: A total of 260 patients were enrolled of which 220 (84.6%) patients developed a total of 425 ADRs. Maximum 51.7% of ADRs were caused by TLE followed by 37% with ZLN regimen. Most common ADRs were dizziness 18.6%, rashes 14.6%, anemia 10.6%, and vomiting 6.6%. Dizziness and rashes are mainly caused by TLE and ZLN regimen, respectively. Management of ADRs with a change in the regimen was applied as an interventional tool in 40% of the patients. Causality assessment as per the WHO-UMC scale showed that 55.5% of ADR were probable and 45.5% were possible. 84.5% of ADR was not preventable, while 15.5% of ADRs were probably preventable. 38% of ADRs were mild, 56% were moderate, and 6% were severe in nature. Conclusion: Antiretrovirals, however, the milestone for the treatment of HIV/AIDS have very high potential for developing ADRs. Hence, active pharmacovigilance is needed for not only safety of the patients but also compliance to the treatment which is necessary for optimal therapeutic outcomes and to improve quality of life.